Alpha thalassaemia in British people. - Higgs, D; Ayyub, H; Clegg, J; Hill, A; Nicholls, R; Teal, H; Wainscoat, J; Weatherall, D (1985)
Although alpha thalassaemia is rare in north Europeans, it has been identified in British people with no known foreign ancestry. Twelve such patients were studied, of whom eight shared a distinctive molecular defect, which was clearly different from defects seen in subjects of Mediterranean or South East Asian origin. A rare but specific form of alpha thalassaemia is therefore present in the British population. In addition, two patients from families of mixed racial origin were encountered who had a moderately severe form of thalassaemia (HbH disease) due to the inheritance of one form of alpha thalassaemia from the British parent and another type from the foreign parent. This shows the importance of careful genetic counselling of British patients with haematological findings of thalassaemia.